A novel Ti–6Al–4V alloy microstructure with very high strength and good ductility. (October 2015) - Jia, M.T.; Zhang, D.L.; Gabbitas, B.; Liang, J.M.; Kong, C.
Graphical abstract: Abstract : This paper reports a novel microstructure consisting of fine and oxygen hardened equiaxed α grains and fine equiaxed transformed β grains hardened by nanometer sized α aciculars, formed by solution treatment, quenching and aging of a Ti–6Al–4V (wt.%) alloy with a relatively high oxygen content of 0.52 wt.%, and produced by powder compact forging. The microstructure renders the alloy with a very high tensile yield strength of 1352.4 MPa, ultimate tensile strength of 1421.7 MPa and elongation to fracture of 7.2%.